Exploring Art-Integrated Learning as A Strategy to Foster Students’ Behavioral Engagement in an EFL classroom (2023)
ABSTRACT: This paper reports an action research project carried out in a public school in the urban area of El Carmen de Viboral, Antioquia. This project aimed at exploring the impact of an Art-Integrated Learning class in the behavioral engagement of an 8th grade class. This project was focused on three aspects of behavioral engagement: Students following instructions, students asking questions, and students contributing to class discussions. For achieving the objective of this projects, different activities mixing both artistic and linguistic tasks were proposed to students. Data collection methods included teacher’s journal, questionnaires, memos, and students’ artifacts. The analysis of these instruments suggested four findings: Students following instructions and efforts to accomplish the tasks, students asking pertinent questions, students contributing to class discussions, and AIL to generate students' reflections and positive feelings in the EFL classroom.